Evaluasi Kinerja Simpang Bersinyal Jl. Dr. Ir. H. Soekarno - Jl. Mulyorejo Surabaya - Rio Dirgo Sirajaya; muhammad shofwan donny cahyono; Yoanita Eka Rahayu (Jurnal Teknik Sipil, 2022)
Crossroads Dr. Ir. H. Soekarno - Jalan Mulyorejo is one of the signalized intersections in the bustling city of Surabaya. The problem at the intersection is the length of the queue and the length of the delay due to the number of vehicles passing through the intersection. The reason for conducting research at the intersection is to assess the performance of traffic at the intersection. Data was collected by means of a direct survey at the research site. The data analyzed are the number of vehicles that pass each intersection approach, signal time, vehicle speed that passes through the intersection, and geometric. The data obtained is used to obtain the current state of the saturation current. The methods and data used will serve as guidelines for conducting analysis and evaluation. The method used to analyze the data using the 1997 Indonesian Road Capacity Manual (MKJI 1997). Based on the analysis and evaluation of the existing condition in 2021 at the peak hours of LOS D in the morning, afternoon and evening. The maximum jam length is 465 m. Morning, afternoon and evening peak time segment Jl. DR.Ir.H. Soekarno LOS D. So it needs improvement starting in 2021-2025 by changing the number of phases and signal times for the morning, afternoon and evening peak intersections. The LOS D level is obtained with a DI ranging from 214 to 268 sec/pcu, the queue length (QL) in 2025 is a maximum of 1973 mKeywords: MKJI 1997, Signal intersection